Determination of the strength indicators of normal blockboard made of post-consumer wood - Medvid, L.M.; Gayda, S.V. (Forestry, Forest, Paper and Woodworking Industry, 2023)
Reasonably, wood resources should be used comprehensively, in particular, this applies to wood waste and residues at all stages of production. But today, as never before, according to the principles of the circular economy, the issue of processing post-consumer wood (PCW) has arisen - an additional reserve of wood that has already lost its consumer characteristics in products, and its disposal minimizes the negative impact on the environment. A batch of PCW-made blockboard was made by implementing the B-plan of the second order, where the variables were the width of the rails of tangential and radial sawing. The limits of strength during static bending and during chipping for PCW-made blockboard spruce wood were experimentally determined and two adequate regression models were built depending on the alternate laying of radial (Brad) and tangential (Btan) rails with widths of 30, 50 and 70 mm at a thickness of 22 mm . It was established that the width of the rails in the construction of carpentry boards significantly affects the strength characteristics of the structure. It was found that an increase in width from 30 to 70 mm during the determination of the strength limit in static bending leads to a decrease in the indicator for radial rails by 15-20%, and for tangential rails - by 33-38%; and during the determination of the limit of rocking strength, it leads to an increase of 15-17% for radial rails, and a decrease of 12-14% for tangential rails. It was established that the strength limit during static bending of all PCW-made blockboard spruce, regardless of their design, meets the requirements of DSTU13715:1978. The limit of strength during chipping for most of the samples of experimental boards also meets the regulatory requirements, except for one, when laying rails with a width of 70 mm. According to the results of experimental studies, it was established that the maximum value of the strength limit during static bending σu = 35.705 MPa can be obtained by fixing the dimensional parameters of the width of the rails PCW-made blockboard from spruce of combined stacking: Brad (x1) = 30 mm Btan (x2) = 30 mm. It was established that the maximum value of the strength limit during chipping τsk = 1.961 MPa, taken as an absolute value, can be obtained by fixing the dimensional parameters of the width of the slats of carpentry boards made of PCW from spruce combined stacking and veneered with plywood: Brad (x1) = 70 mm; Btan (x2) = 48 mm. It is recommended to use post-consumer wood for the production of blockboard with a cross-section of rails in a ratio no larger than 1:4 with a combined arrangement of radial and tangential ones.